Development of nanoemulsions containing penciclovir for herpes simplex treatment and a liquid chromatographic method to drug assessment in porcine skin layers - Alianise da Silva Meira; Ana Paula Battistel; Helder Ferreira Teixeira; Nadia Maria Volpato (Drug Analytical Research, 2020)
A successful formulation (penciclovir hydrogel nanoemulsion - HN) to be used in transdermal drug delivery route to treat herpes simplex virus was developed and an analytical method to quantify penciclovir (PCV) in porcine ear skin was stablished and validated. PCV nanoemulsions were prepared by high pressure homogenization and presented spherical mean droplet size 180 nm. The association efficiency and zeta potential were 87% and– 27 mV, respectively. The bioanalytical method developed showed specificity for the interferences from the skin matrixes (epidermis and dermis) and the linearity was in the range 0.1 – 25 μg/mL of drug, The mean recovery data for the three levels tested were 95.2% for the epidermis and 97.3% for the dermis and adequate results were obtained for repeatability and inter-day precision.  In vitro percutaneous absorption studies with the PCV nanoemulsion and a market cream were conducted employing the porcine skin.The cumulative amounts of PCV permeated from cream and HN, 8 h after dosing, were 2.60 and 4.15 μg/cm², respectively, representing a quite higher flux and a much higher permeability coefficient for the developed formulation. It can be concluded that HN provide a good skin targeting effect and may be a promising carrier for topical delivery of penciclovir.